Effect of Salt Concentration on Fractionation of Proteins Using Ultrafiltration - Narsaiah, K; Agarwal, G P (Journal of Agricultural Engineering, 2006)
Major factors that influence protein separation by ultrafiltration are the physico-chemical properties of proteins such as molecular size, charge, system hydrodynamics and other operating conditions of ultrafiltration such as pH, ionic strength and membrane fouling. The effect of varying the ionic strength on transmission and selectivity in case of binary protein mixture of myoglobin and ovalbumin was studied in stirred cell ultrafiltration unit at pH 7.0. Proteins in permeate and retentate samples were resolved and analyzed by HPLC. The results indicated that increasing ionic strength increasesd the transmission and decreased the selectivity. The selectivity also decreased with increase in pressure.